Effect of Gluten-Free Diet on Serum Antioxidant Levels in Children with Celiac - Mehmet Ali Gül; Fatma Betül Özgeriş; Nezahat Kurt; Burcu Volkan; Ali İşlek; Atilla Çayır (European Journal of Biology)
Objective: Celiac disease (CD) is an inflammatory condition of the small intestine triggered by the consumption of gluten. A strict gluten-free diet (GFD) is the only treatment that can eliminate CD complications. It was aimed to evaluate the effect of a gluten-free diet on serum total glutathione (tGSH) level, superoxide dismutase (SOD), myeloperoxida (MPO), paroxanase (PON-1) and aryl esterase (ARE) activity in patients with celiac disease, an autoimmune disease.Materials and Methods: The study was conducted with 68 participants, 39 of whom were celiac and 29 were healthy. Two groups were formed in patients with celiac disease as newly diagnosed and previously diagnosed and following a gluten-free diet. Blood samples were taken from all participants and tGSH, SOD, MPO, PON-1, and ARE measurements were made spectrophotometrically from serum samples.Results: While no significant change was observed in tGSH, SOD, and ARE levels, MPO activity was observed to be significantly lower in celiac patients compared to healthy controls, while this decrease was found to be higher in the newly diagnosed group. While PON-1 activity was significantly lower in newly diagnosed patients compared to the control group, it was higher in the gluten-compatible diet group.Conclusion: Low MPO values in celiac patients may be insufficient to function by creating oxidative stress in inflammation. While PON-1 values are significantly lower in newly diagnosed celiacs, it can be said that they reach normal values with adherence to a gluten-free diet.